Making Sustainable Agriculture Real in CAP 2020: The Role of Conservation Agriculture - Basch, G. (2013)
Europe is about to redefine its Common Agriculture Policy (CAP) for the near future. The question is whether this redefinition is more a fine-tuning of the existing CAP or whether thorough changes can be expected. Looking back to the last revision of CAP the most notable change is, undoubtedly, the concern about EU and global food security. The revival of the interest in agricultural production already became evident during the Health Check as a consequence of climbing commodity prices in 2007/08. It is therefore no surprise that “rising concerns regarding both EU and global food security” is the first topic to appear in the list of justifications for the need for a CAP reform. Other challenges mentioned in this list such as sustainable management of natural resources, climate change and its mitigation, improvement of competitiveness to withstand globalization and rising price volatility, etc., while not new are considered worthwhile enough to be maintained and reappraised.